Evaluación de una versión abreviada del test de la manchas de tinta de Holtzman - Richaud de Minzi, Maria C. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The results obtained by administering a shortened form of HIT <30 plates) to Argentina subjects is compared with data obtained in a U.S. sample. Further, a comparison is also made between the results obtained in the shortened form and the complete form of HIT.